Technologies used in Smart Grid to implement Power Distribution System - Raja Masood Larik; Mohd Wazir Mustafa (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Recently, the debate has been going on about the role of power plus distribution systems, its technologies for future smart grids in power systems. The emerging of new technologies in smart grid and power distribution systems provide a significant change in terms of reduction the commercial and technical losses, improve the rationalization of electricity tariff. The new technologies in smart grid systems have different capabilities to increase the technological efficiency in power distribution systems. These new technologies are the foreseeable solution to address the power system issues. This paper gives a brief detail of new technologies in smart grid systems for its power distribution systems, benefits and recent challenges. The paper provides a brief detail for new researchers and engineers about new technologies in smart grid systems and how to change traditional distribution systems into new smart systems.